(untitled) - Langan, John (New York, 2005)
This edition, features Langan's renowned clear writing style and wide range of writing assignments and activities that reinforce the four essentials of good writing: Unity, Support, Coherence and Sentence Skills.
Keywords: Reading (Higher education),College readers,Kỹ năng đọc cao đẳng đại học,Đọc giả học thuật